Gobierno digital y rendición de cuentas en la Municipalidad Provincial de Requena 2025 - Rodríguez Santillán, Jessica (2025)
The present study aimed to determine the relationship between digital government and accountability in the Provincial Municipality of Requena 2025. This is a basic research project, with a descriptive-correlational approach and a non-experimental design. The sample consisted of 382 citizens. The results showed that the level of digital government was rated as fair at 25%. This is attributed to the fact that the municipality has occasionally implemented the use of electronic DNI (National Identity Document) to access digital services and, in some cases, the information available on the municipal digital platform is up-to-date. Regarding accountability, a score of 25% was also obtained. This is due to the fact that, on some occasions, the municipality communicates important decisions in a timely and clear manner through various media and occasionally publishes audits and evaluations of municipal management. In conclusion, there was a strong positive correlation between digital government and accountability (coefficient 0.788; p=0.000); There were also statistically significant moderate positive correlations between accountability and the variables digital identity (coefficient 0.661; p=0.000), digital services (coefficient 0.711; p=0.000), data governance (coefficient 0.589; p=0.000), interoperability (coefficient 0.617; p=0.000), and digital security (coefficient 0.508; p=0.000), confirming the validity of the respective hypotheses in all cases.